Tutoría como herramienta académica del desarrollo de competencias transversales - Pàmies García, María Antònia (2015)
The work that we are presenting in this document has its origins in IBEROTEC´s model of tutoring. It evolved from an educational proposal about working with transverse competences that made tutoring a tool for the development of these competences. Tutoring is very important, but secondary, in light of the objectives of the formation that intends to reach a particular graduate profile. In this sense, we saw the necessity of generating four principles to orient academic administration and the actions of tutors and teachers. Thus, what this document proposes is a model of academic administration oriented by the following four ideas: the student is autonomous and Iberotec´s principal idea is to contribute to that; the teachers are “learning provocateurs”, they provoke student´s learning; the work is formative; the institution is facilitating. These principles are more than a declaration of intention; they are a series of criteria for daily decision making and for the design of courses and the action plan for tutoring.